The Alignment of and Gaps between the Needs Analysis, the 2013 Curriculum and Classroom Practice of CLT Approach - Kusumawardani, Anisa Dian; Faridi, Abdurrachman (Universitas Negeri Semarang, 2019)
In designing and evaluating a curriculum, need analysis is the prior action so that it can accommodate students’ need and the result is not disappointing. The dissatisfaction toward graduate students from vocational high school who most of them do not have adequate English skill to work can be assumed that the curriculum as well as the learning process do not consider the students’ needs. This study aimed to investigate the vocational high school students’ needs and its alignment of and gap toward the 2013 Curriculum and the practice of CLT approach. This research is qualitative descriptive research which was conducted at SMK Negeri 1 Semarang toward the students and the teacher. The data were collected by using questionnaire, observation checklist, document analysis guideline and interviews.The result of this study shows the students’ opinion, demand, and reflection toward the English learning process. Meanwhile on the investigation of the teaching learning, it is found that the implementation of the 2013 Curriculum more or less has been accordance with the regulation, on the contrary the CLT approach had not been applied well. The alignments of the needs analysis, the curriculum and the CLT approach lay on the sufficient time allotment of the English subject, the learning activity, promoting active learning, and promoting English usage during the learning process. Meanwhile the gaps between the needs analysis, the curriculum and the CLT approach occur in the lack of productive skill practice, authentic learning media, and the discipline-related learning material.